Discovery of oxazine-linked pyrimidine as an inhibitor of breast cancer growth and metastasis by abrogating NF-κB activation - Yuan, Jie; Narasimhachar, Bhanuprakash C.; Ravish, Akshay; Yang, Li; Zhang, Hua; Wang, Qun; Li, Zhi; Huang, Jun; Wang, Bei; Wang, Geng; Kumar Harish, Keshav; Chinnathambi, Arunachalam; et al. (Frontiers in Oncology, 2024)
Introduction: Nuclear factor kappa (NF-κB) plays a key role in cancer cell proliferation; thus, small molecule inhibitors of NF-κB activity can effectively inhibit breast cancer (BC) progression. We have previously reported oxazine and piperazine-linked pyrimidines as novel anti-cancer agents that can suppress NF-κB activation in BC cells. Moreover, the TRX-01 compound, an oxazine-linked pyrimidine, inhibited MCF-7 cells at a concentration of 9.17 µM in the Alamar Blue assay. Methods: This work involved the analysis of frontier molecular orbitals, HOMO-LUMO interactions, and molecular electrostatic potential for the TRX-01 structure. Additionally, the TRX-01 compound was studied for cytotoxicity, and migration as well as invasion assays were performed on BC cells. Results: Finally, TRX-01 blocked the translocation of NF-κB from the cytoplasm to the nucleus in MCF-7 cells and reduced NF-κB and IκBα levels in a dose-dependent manner. It also suppressed migratory and invasive properties of BC cells. Conclusion: Overall, the data indicates that TRX-01 can function as a novel blocker of BC growth and metastasis by targeting NF-κB activation.